Measuring Technical Efficiency Of The Maghreb Health Care Systems Using Dea Approach - Boumaraf, Lyes (جامعة الوادي - University of Eloued, 2014)
Since the Maghreb health care resources are rather limited, it is of interest to analyze whether any substantial differences in the efficiency can be detected. The study examines technical and scale efficiency of the Maghreb countries using DEA, the more advanced econometric and mathematical programming frontier technique that has been applied to health care systems. The results indicate a divergence in efficiency across countries, which may partly be due to differences in geographic area and Health public spending.
مقال
Keywords: Measuring Technical , the Maghreb Health Care systems